Assessment of the compatibility of wood and plastic with cement for their recycling in cement composites - Andrade, André (2012)
The compatibility between maritime pine wood and cement, and between plastic (LDPE) and cement, was assessed for the recycling of wood and plastic in cement composites. Temperature vs. time profiles of cement setting were registered and compatibility indices were calculated. Results indicate that recycling of plastics in plastic-cement composites does not pose any questions regarding chemical compatibility. However, maritime pine hinders cement setting in some extent. So, in order to manufacture wood-cement composites with recycled wood, physico-mechanical properties of composites must be assessed, too. Foi avaliada a compatibilidade entre a madeira de pinho bravo e o cimento, e entre plástico (LDPE) e cimento, com vista à sua reciclagem na forma de aglomerados com cimento como ligante. Obtiveram-se perfis de temperatura versus tempo da presa do cimento, e calcularam-se índices de compatibilidade. O plástico não tem problemas de compatibilidade com o cimento, e, como tal, a reciclagem de plásticos nesta forma será possível. No caso do pinho, a madeira de facto retarda a presa do cimento em certa extensão. Portanto, as propriedades físico-mecânicas de aglomerados cimento-madeira também deverão ser testadas se se pretender reciclar madeira desta forma.